A rose by any other name? Transdisciplinarity in the context of UK research policy. (January 2015) - Lyall, Catherine; Meagher, Laura; Bruce, Ann
Highlights: We assess transdisciplinary developments in UK research funding policy. We present evidence from five empirical case studies of research investments. UK research funding policy achieves elements of transdisciplinarity. The term 'transdisciplinarity' is not widely used by the UK research community. Capacity building for transdisciplinarity requires leadership and cumulative learning. Abstract: This paper assesses developments in transdisciplinary research in the UK. While we support the thesis that transdisciplinarity is still not mainstream and is rarely supported per se by funders of research, this paper examines the extent to which UK research policy has embraced the concept of transdisciplinarity. Five empirical case studies provide data about the interrelationship between the interdisciplinary and impact or knowledge exchange aspirations of Research Council UK (RCUK) investments. We find evidence that, to an extent, UK research funding policy is achieving some elements of transdisciplinarity in practice, if not in name. Drawing on broader debates about the limitations of knowledge mobilisation and the challenges of conducting interdisciplinary research, we reflect on how the situation has changed since our original 2004 paper. The evidence suggests that the absence of the 'transdisciplinary' label is not necessarily impeding the framing of research funding schemes oriented towards societal issues. Nevertheless, several areas where capacity-building is required, including training for early career interdisciplinary researchers; improved research leadership skills; and the capacity to evaluate the quality of transdisciplinary processes and to learn from such evaluations, are identified.